2020
DOI: 10.14814/phy2.14518
|View full text |Cite
|
Sign up to set email alerts
|

Common carotid pulsatility is deteriorated by autoimmune thyroiditis in children with type 1 diabetes mellitus – A pilot study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Unfortunately, there are few and often contrasting results about the effect of AT and CD on the development of early atherosclerosis in patients with T1D. Some small studies have demonstrated that AT and CD affects carotid intima-media thickness (IMT) [ 8 , 9 ], arterial stiffness [ 10 ], carotid pulsatility [ 11 ], and microvascular abnormalities [ 12 , 13 ]. Conversely, the endothelial function seems to be not blunted by the coexistence of T1D and AT [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there are few and often contrasting results about the effect of AT and CD on the development of early atherosclerosis in patients with T1D. Some small studies have demonstrated that AT and CD affects carotid intima-media thickness (IMT) [ 8 , 9 ], arterial stiffness [ 10 ], carotid pulsatility [ 11 ], and microvascular abnormalities [ 12 , 13 ]. Conversely, the endothelial function seems to be not blunted by the coexistence of T1D and AT [ 10 ].…”
Section: Introductionmentioning
confidence: 99%